Dissolution of "The Committee": Mentalization and Psychic Transformation in the Case Of Olav - Malitzky, Max S. (Pragmatic Case Studies in Psychotherapy, 2010)
Stalsett, Engedal, and Austad’s (2010) case study of Olav demonstrates how a treatment integrating the insights and techniques from a wide variety of traditions helped resolve the symptoms in a man with treatment resistant, psychotic depression and a host of underlying personality problems. This commentary focuses on highlighting the change in Olav’s ability to mentalize and consequently to begin to transform his deeply held representations of self and object.